Optimization of the maintenance strategies of roads in Morocco: calibration study of the degradations models of the highway development and management (HDM-4) for flexible pavements. Issue Volume 20:Issued 2(2019) (1st February 2019) - Bannour, Abdelilah; El Omari, Mohamed; Lakhal, El Khadir; Afechkar, Mohamed; Benamar, Ahmed; Joubert, Pierre
ABSTRACT: The Highway Development and Management 4 (HDM-4) model was developed by the World Bank and used for pavements management system. An approach of the adaptation to local conditions is therefore required by adjusting the calibration factors, with the consideration of the context in which they are to be applied. The aim of the present work is to suggest these calibration factors for predicting the deterioration (structural cracking, ravelling, potholes and their resultant roughness) of roads in Morocco. The careful choice of such maintenance work planning is based on the result of these models. This study is based on the exploitation of road database, obtained from visual inspections and measurements performed by the National Center of Road Study and Research. The monitoring covered 6 years and concerned 55 test sections located on the Moroccan territory. Four kinds of structures were analysed involving different pavement bodies, constituting materials and thicknesses. The used method is based on a statistical analysis using equations implemented in HDM-4 models. The calibration process of the pavement behaviour was performed by a linear regression between the predicted values and observed values. Thereafter, the calibration factors for the initiation and the propagation of each damage in the models were determined. The obtained results allow us performing a quite good calibration for a pertinent use of HDM-4 in the local context.